An Analysis of Think Globally-Act Locally Strategy Implementation in Developing Relationship of Headquarters and Subsidiaries: Case Study of John Clements Consultants Inc., Philippines & Indonesia - Dilla Noverita (Gadjah Mada International Journal of Business, 2007)
John Clements Consultants Inc. (JCCI) is a long established and the largest consulting company in Philippines. Its main business focuses on human resource development, especially recruitment and training. Headquarters is in Philippines and its business has grown throughout the world, especially in the Asia-Pacific, Middle-East and United States. As a multinational company, JCCI has to maintain and develop the relationship with all subsidiaries efficiently. In this case, using qualitative approach and focusing on the relationship with Indonesian subsidiary, this research assesses how headquarters of JCCI formulates and implements company policies governing the relationship between headquarters and subsidiaries. It explores how the headquarters controls, communicates, makes decisions, plans strategy, and gives authority to the subsidiaries.  Moreover, this research analyses how JCCI applies “think globally – act locally” strategy in its global operations and developing relationship with subsidiaries. It brings the issues of all challenges and obstacles the company has in dealing with subsidiaries. Finally, this research recommends alternative strategies to leverage the relationship between headquarters and subsidiaries more efficiently and to minimize the obstacles in cross-cultural management so that the company will be able to strengthen its position in global service market.